Kotler’s Decision-Making Model as a Predictor of the Consumer Buying Behavior of Young Professionals in the Philippines - Jefferson Marcelo; Markdolf C. Maliwat; Ivan Dean S. Salacata (International Journal of Marketing and Digital Creative, 2024)
The first stage in creating effective marketing strategies is to analyze consumer behavior in the market with regard to needs, attitudes, or behaviors as well as the influence of the environment. The researchers conducted this study to determine Kotler's decision-making model as a Predictor of Consumer Food Buying Behavior. This research aims to determine the perception of the respondents on how they purchase items in terms of the Kotler's Decision-Making Model and how the consumer evaluates the purchase of food items through their behavior. To determine the relationship between the consumer's behaviors based on Kotler's Decision-Making Model, the researchers used a descriptive design to gather quantifiable data for factual examination of the population sample. The respondents of this study are young professionals working and purchasing food items and living at the three (3) chosen barangay such as Barangay Poblacion, Guadalupe Viejo, and Guadalupe Nuevo. The total population of the study was 100 respondents. The researchers formulate a survey questionnaire through google forms for the data gathering procedure. This research shows a significant relationship between the customer behaviors during the journey and consumer buying behavior using Kotler's Decision-Making model. It shows only that attitude, norms, and intention play a significant role when a consumer decides whether to purchase or not the items. Culture, demand, and willingness to engage or buy the product are vital in the decision-making process. Finally, based on the study's findings, business strategies have been proposed that can be utilized by the business owners and marketing strategist for their business or companies employed.